A Holistic State Estimation Framework for Active Distribution Network with Battery Energy Storage System - Shaojian Song; Huangjiao Wei; Yuzhang Lin; Cheng Wang; Antonio Gomez-Exposito (Journal of Modern Power Systems and Clean Energy, 2022)
Battery energy storage systems (BESSs) are expected to play a crucial role in the operation and control of active distribution networks (ADNs). In this paper, a holistic state estimation framework is developed for ADNs with BESSs integrated. A dynamic equivalent model of BESS is developed, and the state transition and measurement equations are derived. Based on the equivalence between the correction stage of the iterated extended Kalman filter (IEKF) and the weighted least squares (WLS) regression, a holistic state estimation framework is proposed to capture the static state variables of ADNs and the dynamic state variables of BESSs, especially the state of charge (SOC). A bad data processing method is also presented. The simulation results show that the proposed holistic state estimation framework improves the accuracy of state estimation as well as the capability of bad data detection for both ADNs and BESSs, providing comprehensive situational awareness for the whole system.